Autonomous Civil Action and Regulatory Transparency in Support of Substantive Democratic Reform - Indira Jazmine; Edward Benedictus Roring; Wicipto Setiadi (TEKTONIK : Jurnal Ilmu Teknik, 2026)
This study examines the interaction between civil society and the state in strengthening substantive democracy, emphasizing democratic practices that go beyond elections. Using a qualitative approach supported by a focused literature review, the research analyzes how civic engagement, state responsiveness, and institutional transparency contribute to deeper democratic outcomes. The findings show that substantive democracy grows when civil society remains autonomous, inclusive, and capable of influencing decision-making, while the state provides an enabling environment that protects civic freedoms. The study concludes that strong state–society synergy is essential for advancing accountability, participation, and social justice within democratic systems.